Cannabinoids Ameliorate Impairments Induced by Chronic Stress to Synaptic Plasticity and Short-Term Memory - Abush, Hila (Nature Publishing Group, 2013)
Repeated stress is one of the environmental factors that precipitates and exacerbates mental illnesses like depression and anxiety as well as cognitive impairments. We have previously shown that cannabinoids can prevent the effects of acute stress on learning and memory. Here we aimed to find whether chronic cannabinoid treatment would alleviate the long-term effects of exposure to chronic restraint stress on memory and plasticity as well as on behavioral and neuroendocrine measures of anxiety and depression. Late adolescent rats were exposed to chronic restraint stress for 2 weeks followed each day by systemic treatment with vehicle or with the CB1/2 receptor agonist WIN55,212-2 (1.2 mg/kg). Thirty days after the last exposure to stress, rats demonstrated impaired long-term potentiation (LTP) in the ventral subiculum-nucleus accumbens (NAc) pathway, impaired performance in the prefrontal cortex (PFC)-dependent object-recognition task and the hippocampal-dependent spatial version of this task, increased anxiety levels, and significantly reduced expression of glucocorticoid receptors (GRs) in the amygdala, hippocampus, PFC, and NAc. Chronic WIN55,212-2 administration prevented the stress-induced impairment in LTP levels and in the spatial task, with no effect on stress-induced alterations in unconditioned anxiety levels or GR levels. The CB1 antagonist AM251 (0.3 mg/kg) prevented the ameliorating effects of WIN55,212-2 on LTP and short-term memory. Hence, the beneficial effects of WIN55,212-2 on memory and plasticity are mediated by CB1 receptors and are not mediated by alterations in GR levels in the brain areas tested. Our findings suggest that cannabinoid receptor activation could represent a novel approach to the treatment of cognitive deficits that accompany a variety of stress-related neuropsychiatric disorders.